Study on ferritin and liver injury in pediatric hemophagocytic lymphohistiocytosis associated with infection - Gailing Hao; Quanheng Li; Nan Zhang; Weili Guo; Xiao Wang; Wenjin Geng (Scientific Reports)
Abstract Summarize and analyze the clinical characteristics of children with infection-associated hemophagocytic lymphohistiocytosis (IAHLH) complicated by liver injury, and investigate the correlation between ferritin (FERR) and liver injury indicators. A total of 90 children with IAHLH admitted to Hebei Children’s Hospital from November 1, 2017 to September 30, 2024 were selected as the research subjects. The patients were divided into liver injury group and non-liver injury group based on the presence of liver damage. The clinical features and laboratory test differences between the two groups were analyzed, and the correlation between ferritin and liver injury markers was investigated. (1) Among the 90 cases of IAHLH, 61cases (67.8%) were complicated by liver injury. In the liver injury group, FERR and D-dimer (DD) were significantly higher than those in the non-liver injury group (P < 0.05), while fibrinogen (FIB) and albumin were significantly lower (P < 0.05). Moreover, the liver injury group was more likely to develop to multiple organ dysfunction syndrome (MODS) (P = 0.021). (2) FERR was positively correlated with indicators such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and DD (P < 0.05), and negatively correlated with indicators such as albumin (ALB) (P < 0.05). FERR has a certain correlation with liver injury in pediatric hemophagocytic lymphohistiocytosis associated with infection. Monitoring FERR can help evaluate the degree of liver injury and alert to the occurrence of MODS, providing a basis for early clinical intervention.